Prevalence of Indices of Stress with Degree of Insomnia and Academic Performance in Undergraduate Medical Students (Journal of Fatima Jinnah Medical University, 2023)
Background: Studying medicine is quite challenging as medical students have to work hours and hours which leads to continuous psychological stress and as a result decrease in sleep duration and quality. This study aims to determine the prevalence as well as the relationship of academic stress and pattern of sleeping problems among medical students.Subjects and Methods: In this cross-sectional study,128 non-obese medical students (18 -23 years old, BMI=18.5-24.9) are included and they are divided into 2 groups as non-stressed (K10≤19) and stressed (K10>19) medical students. We have used Kessler Psychological Distress Scale(K10), Pittsburgh Sleep Quality Index Scale (PSQI) and percentage of Professional Examination Result to assess stress, sleep quality and academic performance, respectively.Results: PSQI scores were less in the stressed[8.5(3─17)] as compared to non-stressed [6(1─17)] subjects (p=0.000) while academic score (percentage) in stressed [70.9(59─77)] was lesser than that of non-stressed[76.7(57─86)] subjects (p=0.000).Within the non-stressed subjects,K10 scores were positively correlated to PSQI scores (rho=0.294, p=0.018) and negatively correlated to academic score (rho= -0.319, p=0.010).Similarly in the stressed subjects there was a positive correlation between K10 and PSQI scores (rho=0.435, p=0.000) and a negative correlation between K10 and academic scores( rho= -0.251, p=0.045)Conclusion: This study suggests that both sleep quality and academic performance reduces with increase in stress among non-obese medical students.Keywords: stress, non-obese, medical students, sleep quality, academic performance.
Keywords: Stress; Non obese; Medical Students; Sleep quality; Academic performance